Context-Considered Leadership Development: Quasi-Experiment in a Russian Mining Company - Marina Kravtsuk (Indonesian Journal of Sustainability Accounting and Management, 2022)
Scholars argued that leadership development approaches should be deeply contextualized and explain how to develop leadership. This article aimed to answer a research question: how to develop leadership in the context of a Russian mining organization. For that purpose, a quasi-experiment using a pre-and post-intervention was conducted in a Russian mining organization by an immersed researcher. Multiple levels of management were involved. Multifactor Leadership Questionnaire was used as a major measurement tool for leadership styles and effectiveness that had objective criteria. The results indicate that the leadership development was driven by the executives and mirrored by middle managers and supervisors. A cascade of frequency of utilization of leadership styles was observed, which led to an increase in effectiveness. Generally, the intervention caused statistically significant changes with low-to-large effect sizes. To the best of the author’s knowledge, no similar studies were conducted with the reported level of contextualization and details, allowing us to expand the body of knowledge and provide guidance for the practice of leadership development. The study limitations include the following: research was conducted in a real-life context and could be difficult to repeat. The author acted as an associate of the managers, and effectiveness measures transactional outcomes.